PENGARUH APLIKASI HERBISIDA GROMOXONE 276 SL (LARUT) TERHADAP SIFAT KIMIA INCEPTISOL - Maidia Solfianti; Amsar Maulana; H Herviyanti; Teguh Budi Prasetyo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Gromoxone 267 SL Herbicide (GH) is widely used in weed control, and its contamination in the soil has the potential for contamination in agricultural land. The purpose of this study was to explore the effect of the application of soluble Gromoxone 267 SL herbicide on changes in the chemical properties of Inceptisols. This study used a completely randomized design with 4 treatments and 3 replications, namely A = 0% R (0.00 mL GH 7.34 mL H2O); B = 50% R (0.03 mL GH 7.34 mL-1 H2O); C = 100% R (0.06 mL-1 HG 7.34 mL-1 H2O) and D = 150% R (0.09 mL HG 7.34 mL-1 H2O), where 100% recommended soluble Gromoxone 267 SL herbicide (soluble) is assumed to be equivalent to ( ) 100% Paraquat Dichloride (276 g L-1) in the Gromoxone 267 SL herbicide. The results of this study showed that 150% application of the recommended soluble Gromoxone 267 SL herbicide had a very significant effect on reducing CEC, total N, K, Ca and Mg-dd. It also had a significant effect on organic C and N of Inceptisols compared with control or without application of Gromoxone 267 SL herbicide.